2013
DOI: 10.1103/physrevb.87.085414
|View full text |Cite
|
Sign up to set email alerts
|

Laser and voltage manipulation of bistable Si dopants in the GaAs (110) surface

Abstract: Bistable behavior of single Si dopants in the (110) surface layer of GaAs was studied with a scanning tunneling microscope (STM). The Si atom acts as either a positively charged substitutional donor or a negatively charged interstitial. Its configuration can switch under the influence of a local biased STM tip. To independently manipulate the charge state, the sample was illuminated by a laser during STM operation. The Si atom can be reversibly switched between its positive and negative charge states by turnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Previous studies 5 27 have shown that under dark conditions bistable charging processes of doping atoms have to be taken into account. Assuming that these processes define the noise level of the spectra without optical excitation, our results suggest that the presence of free electron–hole pairs suppresses this charge switching in the photoexcited case 9 26 . We like to point out that the decrease in noise in comparison to the noise under dark conditions is not the result of a simple decrease of the SCR.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies 5 27 have shown that under dark conditions bistable charging processes of doping atoms have to be taken into account. Assuming that these processes define the noise level of the spectra without optical excitation, our results suggest that the presence of free electron–hole pairs suppresses this charge switching in the photoexcited case 9 26 . We like to point out that the decrease in noise in comparison to the noise under dark conditions is not the result of a simple decrease of the SCR.…”
Section: Resultsmentioning
confidence: 78%
“…For regime II, σ RMS increases. We attribute this to a non-equilibrium charging and discharging process of dopants 4 5 9 26 inside the SCR ( Fig. 1a,d ) due to the carrier injection.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, bistable behavior of Si atoms in the (110) surface layer of GaAs was observed during scanning with a STM tip [15,16]. Only and all the Si dopants in the surface layer exhibit this behavior; the dopants below the surface do not.…”
mentioning
confidence: 99%
“…The Si charge state is nonvolatile at low temperatures, which enables the storage of information [16]. For memory operation, three separate conditions need to be distinguished: (a) setting the system to Si − i , (b) setting it to Si + d , and (c) detecting the charge state.…”
mentioning
confidence: 99%
“…For regime II, σ RMS increases. We attribute this to a nonequilibrium charging and discharging process of dopants 19,87,91,96 inside the SCR due to the carrier injection. By disturbing the hole density at the surface by valence band tunnelling I V drives the SCR in metastable configurations.…”
Section: Noise Analysis Of the Nanoscaled Space Charge Regionmentioning
confidence: 97%